1990
DOI: 10.1212/wnl.40.3_part_1.500
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid production is reduced in healthy aging

Abstract: In order to study age-related differences in cerebrospinal fluid (CSF) production in humans, we measured the rate of CSF production in 7 young (age 21 to 36 years) and 7 elderly (age 67 to 84 years) healthy volunteers, using a modified Masserman method. In addition, we evaluated CSF protein gradients by collecting CSF in serial fractions up to the 30th ml and assaying for total protein concentration. The mean rate of CSF production was significantly less in the elderly than in the young subjects. Mean CSF tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
172
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(188 citation statements)
references
References 0 publications
14
172
1
1
Order By: Relevance
“…Whether this is an indirect effect due to overall dysregulation of genes involved in cholesterol homeostasis remains to be determined. Modification of the choroid plexus with age is related to a lower rate of CSF secretion in elderly individuals (32,33). In Alzheimer's disease, there is thickening of the basement membrane of the choroid plexus and flattening of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is an indirect effect due to overall dysregulation of genes involved in cholesterol homeostasis remains to be determined. Modification of the choroid plexus with age is related to a lower rate of CSF secretion in elderly individuals (32,33). In Alzheimer's disease, there is thickening of the basement membrane of the choroid plexus and flattening of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among older volunteers, no significant difference has been shown between other cognitive disorders and CSF flow rate, and thus the prediction of the potential benefit from surgery. Some consider flow velocity and rate measurements adequate for a differential diagnosis and the prediction of the benefit from surgery, but others think the opposite (4,11,14,17).…”
Section: Discussionmentioning
confidence: 99%
“…Various parameters, i.e., time, velocity, and flow, have been used to examine CSF flow dynamics (8,14,10,20). There are differing opinions as to whether measuring aqueductal CSF flow velocity and flow rate contributes to a differential diagnosis of NPH or on in the decision-making regarding shunt therapy (6).…”
Section: Discussionmentioning
confidence: 99%
“…May et al [27] found in elderly healthy individuals a significantly lower CSF production compared with healthy young subjects.…”
Section: Figure 25 Choroid Plexus and Arachnoid Granulations Adaptementioning
confidence: 96%
“…Invasive methods and imaging-based approaches have reported a large range of results (0.35 -0.7 ml/min) [26][27][28][29][30].…”
Section: Figure 25 Choroid Plexus and Arachnoid Granulations Adaptementioning
confidence: 99%